Engineering triterpene metabolism in tobacco - Shuiqin, Wu (2012)
Terpenes comprise a distinct class of natural products that serve a diverse range of physiological functions, provide for interactions between plants and their environment and represent a resource for many kinds of practical applications. To better appreciate the importance of terpenes to overall growth and development, and to create a production capacity for specific terpenes of industrial interest, we have pioneered the development of strategies for diverting carbon flow from the native terpene biosynthetic pathways operating in the cytosol and plastid compartments of tobacco for the generation of specific classes of terpenes. In the current work, we demonstrate how difficult it is to divert the 5-carbon intermediates DMAPP and IPP from the mevalonate pathway operating in the cytoplasm for triterpene biosynthesis, yet diversion of the same intermediates from the methylerythritol phosphate pathway operating in the plastid compartment leads to the accumulation of very high levels of the triterpene squalene. This was assessed by the co-expression of an avian farnesyl diphosphate synthase and yeast squalene synthase genes targeting metabolism in the cytoplasm or chloroplast. We also evaluated the possibility of directing this metabolism to the secretory trichomes of tobacco by comparing the effects of trichome-specific gene promoters to strong, constitutive viral promoters. Surprisingly, when transgene expression was directed to trichomes, high-level squalene accumulation was observed, but overall plant growth and physiology were reduced up to 80 % of the non-transgenic controls. Our results support the notion that the biosynthesis of a desired terpene can be dramatically improved by directing that metabolism to a non-native cellular compartment, thus avoiding regulatory mechanisms that might attenuate carbon flux within an engineered pathway.